Termination w.r.t. Q of the following Term Rewriting System could not be shown:
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
Q is empty.
Using Dependency Pairs [1,15] we result in the following initial DP problem:
Q DP problem:
The TRS P consists of the following rules:
B(a(b(b(a(b(x1)))))) → B(b(x1))
B(b(b(b(x1)))) → B(a(b(x1)))
B(b(b(b(x1)))) → B(b(a(b(x1))))
B(a(b(b(a(b(x1)))))) → B(a(b(b(x1))))
B(b(b(b(x1)))) → B(b(b(a(b(x1)))))
B(a(b(b(a(b(x1)))))) → B(b(a(b(b(x1)))))
The TRS R consists of the following rules:
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B(a(b(b(a(b(x1)))))) → B(b(x1))
B(b(b(b(x1)))) → B(a(b(x1)))
B(b(b(b(x1)))) → B(b(a(b(x1))))
B(a(b(b(a(b(x1)))))) → B(a(b(b(x1))))
B(b(b(b(x1)))) → B(b(b(a(b(x1)))))
B(a(b(b(a(b(x1)))))) → B(b(a(b(b(x1)))))
The TRS R consists of the following rules:
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By using the rule removal processor [15] with the following polynomial ordering [25], at least one Dependency Pair or term rewrite system rule of this QDP problem can be strictly oriented.
Strictly oriented dependency pairs:
B(a(b(b(a(b(x1)))))) → B(b(x1))
B(b(b(b(x1)))) → B(a(b(x1)))
B(b(b(b(x1)))) → B(b(a(b(x1))))
B(a(b(b(a(b(x1)))))) → B(a(b(b(x1))))
Used ordering: POLO with Polynomial interpretation [25]:
POL(B(x1)) = 2·x1
POL(a(x1)) = x1
POL(b(x1)) = 2 + 2·x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B(b(b(b(x1)))) → B(b(b(a(b(x1)))))
B(a(b(b(a(b(x1)))))) → B(b(a(b(b(x1)))))
The TRS R consists of the following rules:
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 1 SCC with 1 less node.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B(b(b(b(x1)))) → B(b(b(a(b(x1)))))
The TRS R consists of the following rules:
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule B(b(b(b(x1)))) → B(b(b(a(b(x1))))) at position [0] we obtained the following new rules:
B(b(b(b(a(b(b(a(b(x0))))))))) → B(b(b(a(b(b(a(b(b(x0)))))))))
B(b(b(b(b(b(b(x0))))))) → B(b(b(a(b(b(b(a(b(x0)))))))))
B(b(b(b(b(a(b(x0))))))) → B(b(b(b(a(b(b(x0)))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B(b(b(b(b(b(b(x0))))))) → B(b(b(a(b(b(b(a(b(x0)))))))))
B(b(b(b(a(b(b(a(b(x0))))))))) → B(b(b(a(b(b(a(b(b(x0)))))))))
B(b(b(b(b(a(b(x0))))))) → B(b(b(b(a(b(b(x0)))))))
The TRS R consists of the following rules:
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The finiteness of this DP problem is implied by strong termination of a SRS due to [12].
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
B(b(b(b(b(b(b(x0))))))) → B(b(b(a(b(b(b(a(b(x0)))))))))
B(b(b(b(a(b(b(a(b(x0))))))))) → B(b(b(a(b(b(a(b(b(x0)))))))))
B(b(b(b(b(a(b(x0))))))) → B(b(b(b(a(b(b(x0)))))))
Q is empty.
We have reversed the following QTRS:
The set of rules R is
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
B(b(b(b(b(b(b(x0))))))) → B(b(b(a(b(b(b(a(b(x0)))))))))
B(b(b(b(a(b(b(a(b(x0))))))))) → B(b(b(a(b(b(a(b(b(x0)))))))))
B(b(b(b(b(a(b(x0))))))) → B(b(b(b(a(b(b(x0)))))))
The set Q is empty.
We have obtained the following QTRS:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
The set Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
Using Dependency Pairs [1,15] we result in the following initial DP problem:
Q DP problem:
The TRS P consists of the following rules:
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(b(a(b(b(a(b(b(B(x)))))))))
B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x)))))
B1(b(b(b(b(b(B(x))))))) → B1(b(a(b(b(B(x))))))
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(a(b(b(B(x)))))
B1(a(b(b(b(b(B(x))))))) → B1(a(b(b(b(B(x))))))
B1(b(b(b(x)))) → B1(a(b(b(b(x)))))
B1(b(b(b(b(b(B(x))))))) → B1(a(b(b(b(a(b(b(B(x)))))))))
B1(a(b(b(a(b(x)))))) → B1(a(b(b(x))))
B1(a(b(b(a(b(x)))))) → B1(b(x))
B1(a(b(b(b(b(B(x))))))) → B1(b(a(b(b(b(B(x)))))))
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(b(a(b(b(B(x))))))
B1(b(b(b(b(b(B(x))))))) → B1(b(b(a(b(b(B(x)))))))
B1(b(b(b(b(b(B(x))))))) → B1(a(b(b(B(x)))))
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(a(b(b(a(b(b(B(x))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(b(a(b(b(a(b(b(B(x)))))))))
B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x)))))
B1(b(b(b(b(b(B(x))))))) → B1(b(a(b(b(B(x))))))
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(a(b(b(B(x)))))
B1(a(b(b(b(b(B(x))))))) → B1(a(b(b(b(B(x))))))
B1(b(b(b(x)))) → B1(a(b(b(b(x)))))
B1(b(b(b(b(b(B(x))))))) → B1(a(b(b(b(a(b(b(B(x)))))))))
B1(a(b(b(a(b(x)))))) → B1(a(b(b(x))))
B1(a(b(b(a(b(x)))))) → B1(b(x))
B1(a(b(b(b(b(B(x))))))) → B1(b(a(b(b(b(B(x)))))))
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(b(a(b(b(B(x))))))
B1(b(b(b(b(b(B(x))))))) → B1(b(b(a(b(b(B(x)))))))
B1(b(b(b(b(b(B(x))))))) → B1(a(b(b(B(x)))))
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(a(b(b(a(b(b(B(x))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 1 SCC with 8 less nodes.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(b(a(b(b(a(b(b(B(x)))))))))
B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x)))))
B1(b(b(b(x)))) → B1(a(b(b(b(x)))))
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(a(b(b(a(b(b(B(x))))))))
B1(a(b(b(a(b(x)))))) → B1(b(x))
B1(a(b(b(a(b(x)))))) → B1(a(b(b(x))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By using the rule removal processor [15] with the following polynomial ordering [25], at least one Dependency Pair or term rewrite system rule of this QDP problem can be strictly oriented.
Strictly oriented dependency pairs:
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(a(b(b(a(b(b(B(x))))))))
B1(a(b(b(a(b(x)))))) → B1(b(x))
B1(a(b(b(a(b(x)))))) → B1(a(b(b(x))))
Used ordering: POLO with Polynomial interpretation [25]:
POL(B(x1)) = x1
POL(B1(x1)) = x1
POL(a(x1)) = x1
POL(b(x1)) = 1 + x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(a(b(b(a(b(b(b(B(x))))))))) → B1(b(a(b(b(a(b(b(B(x)))))))))
B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x)))))
B1(b(b(b(x)))) → B1(a(b(b(b(x)))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule B1(a(b(b(a(b(b(b(B(x))))))))) → B1(b(a(b(b(a(b(b(B(x))))))))) at position [0] we obtained the following new rules:
B1(a(b(b(a(b(b(b(B(y0))))))))) → B1(b(b(a(b(b(b(B(y0))))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x)))))
B1(b(b(b(x)))) → B1(a(b(b(b(x)))))
B1(a(b(b(a(b(b(b(B(y0))))))))) → B1(b(b(a(b(b(b(B(y0))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 1 SCC with 1 less node.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x)))))
B1(b(b(b(x)))) → B1(a(b(b(b(x)))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule B1(b(b(b(x)))) → B1(a(b(b(b(x))))) at position [0,0] we obtained the following new rules:
B1(b(b(b(b(b(b(b(b(B(x0)))))))))) → B1(a(b(b(b(a(b(b(b(a(b(b(B(x0)))))))))))))
B1(b(b(b(a(b(b(b(b(B(x0)))))))))) → B1(a(b(b(b(b(a(b(b(b(B(x0)))))))))))
B1(b(b(b(b(x0))))) → B1(a(b(a(b(b(b(x0)))))))
B1(b(b(b(b(b(b(x0))))))) → B1(a(b(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(a(b(b(a(b(b(b(B(x0)))))))))))) → B1(a(b(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(b(b(b(b(b(b(B(x0)))))))) → B1(a(b(a(b(b(b(a(b(b(B(x0)))))))))))
B1(b(b(b(a(b(b(a(b(x0))))))))) → B1(a(b(b(b(b(a(b(b(x0)))))))))
B1(b(b(b(b(b(b(b(B(x0))))))))) → B1(a(b(b(a(b(b(b(a(b(b(B(x0))))))))))))
B1(b(b(b(b(b(x0)))))) → B1(a(b(b(a(b(b(b(x0))))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(b(b(b(b(b(b(b(b(B(x0)))))))))) → B1(a(b(b(b(a(b(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x)))))
B1(b(b(b(b(b(b(x0))))))) → B1(a(b(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(b(x0))))) → B1(a(b(a(b(b(b(x0)))))))
B1(b(b(b(a(b(b(b(b(B(x0)))))))))) → B1(a(b(b(b(b(a(b(b(b(B(x0)))))))))))
B1(b(b(b(a(b(b(a(b(b(b(B(x0)))))))))))) → B1(a(b(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(b(b(b(b(b(b(B(x0)))))))) → B1(a(b(a(b(b(b(a(b(b(B(x0)))))))))))
B1(b(b(b(a(b(b(a(b(x0))))))))) → B1(a(b(b(b(b(a(b(b(x0)))))))))
B1(b(b(b(b(b(b(b(B(x0))))))))) → B1(a(b(b(a(b(b(b(a(b(b(B(x0))))))))))))
B1(b(b(b(b(b(x0)))))) → B1(a(b(b(a(b(b(b(x0))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 1 SCC with 3 less nodes.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x)))))
B1(b(b(b(b(b(b(x0))))))) → B1(a(b(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(b(x0))))) → B1(a(b(a(b(b(b(x0)))))))
B1(b(b(b(a(b(b(b(b(B(x0)))))))))) → B1(a(b(b(b(b(a(b(b(b(B(x0)))))))))))
B1(b(b(b(a(b(b(a(b(b(b(B(x0)))))))))))) → B1(a(b(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(b(b(b(a(b(b(a(b(x0))))))))) → B1(a(b(b(b(b(a(b(b(x0)))))))))
B1(b(b(b(b(b(x0)))))) → B1(a(b(b(a(b(b(b(x0))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule B1(b(b(b(a(b(b(b(b(B(x0)))))))))) → B1(a(b(b(b(b(a(b(b(b(B(x0))))))))))) at position [0,0] we obtained the following new rules:
B1(b(b(b(a(b(b(b(b(B(y0)))))))))) → B1(a(b(a(b(b(b(a(b(b(b(B(y0))))))))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x)))))
B1(b(b(b(b(x0))))) → B1(a(b(a(b(b(b(x0)))))))
B1(b(b(b(b(b(b(x0))))))) → B1(a(b(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(a(b(b(a(b(b(b(B(x0)))))))))))) → B1(a(b(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(b(b(b(a(b(b(a(b(x0))))))))) → B1(a(b(b(b(b(a(b(b(x0)))))))))
B1(b(b(b(a(b(b(b(b(B(y0)))))))))) → B1(a(b(a(b(b(b(a(b(b(b(B(y0))))))))))))
B1(b(b(b(b(b(x0)))))) → B1(a(b(b(a(b(b(b(x0))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 1 SCC with 1 less node.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x)))))
B1(b(b(b(b(b(b(x0))))))) → B1(a(b(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(b(x0))))) → B1(a(b(a(b(b(b(x0)))))))
B1(b(b(b(a(b(b(a(b(b(b(B(x0)))))))))))) → B1(a(b(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(b(b(b(a(b(b(a(b(x0))))))))) → B1(a(b(b(b(b(a(b(b(x0)))))))))
B1(b(b(b(b(b(x0)))))) → B1(a(b(b(a(b(b(b(x0))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule B1(a(b(b(a(b(x)))))) → B1(b(a(b(b(x))))) at position [0] we obtained the following new rules:
B1(a(b(b(a(b(b(b(b(b(B(x0))))))))))) → B1(b(a(b(a(b(b(b(a(b(b(B(x0))))))))))))
B1(a(b(b(a(b(b(b(x0)))))))) → B1(b(a(b(a(b(b(b(x0))))))))
B1(a(b(b(a(b(a(b(x0)))))))) → B1(b(b(a(b(b(x0))))))
B1(a(b(b(a(b(b(b(b(b(b(B(x0)))))))))))) → B1(b(a(b(b(a(b(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(a(b(b(b(B(x0))))))))))) → B1(b(b(a(b(b(a(b(b(B(x0))))))))))
B1(a(b(b(a(b(b(b(B(x0))))))))) → B1(b(b(a(b(b(b(B(x0))))))))
B1(a(b(b(a(b(b(b(b(x0))))))))) → B1(b(a(b(b(a(b(b(b(x0)))))))))
B1(a(b(b(a(b(a(b(b(a(b(b(b(B(x0)))))))))))))) → B1(b(a(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(a(b(b(b(b(B(x0)))))))))))) → B1(b(a(b(b(b(a(b(b(b(B(x0)))))))))))
B1(a(b(b(a(b(a(b(b(a(b(x0))))))))))) → B1(b(a(b(b(b(a(b(b(x0)))))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(a(b(b(a(b(b(b(b(b(B(x0))))))))))) → B1(b(a(b(a(b(b(b(a(b(b(B(x0))))))))))))
B1(b(b(b(b(b(b(x0))))))) → B1(a(b(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(a(b(b(a(b(b(b(B(x0)))))))))))) → B1(a(b(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(b(b(x0)))))))) → B1(b(a(b(a(b(b(b(x0))))))))
B1(a(b(b(a(b(a(b(x0)))))))) → B1(b(b(a(b(b(x0))))))
B1(a(b(b(a(b(b(b(b(b(b(B(x0)))))))))))) → B1(b(a(b(b(a(b(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(b(b(b(x0))))))))) → B1(b(a(b(b(a(b(b(b(x0)))))))))
B1(a(b(b(a(b(a(b(b(a(b(b(b(B(x0)))))))))))))) → B1(b(a(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(b(b(b(b(b(x0)))))) → B1(a(b(b(a(b(b(b(x0))))))))
B1(a(b(b(a(b(a(b(b(a(b(x0))))))))))) → B1(b(a(b(b(b(a(b(b(x0)))))))))
B1(b(b(b(b(x0))))) → B1(a(b(a(b(b(b(x0)))))))
B1(b(b(b(a(b(b(a(b(x0))))))))) → B1(a(b(b(b(b(a(b(b(x0)))))))))
B1(a(b(b(a(b(a(b(b(b(B(x0))))))))))) → B1(b(b(a(b(b(a(b(b(B(x0))))))))))
B1(a(b(b(a(b(b(b(B(x0))))))))) → B1(b(b(a(b(b(b(B(x0))))))))
B1(a(b(b(a(b(a(b(b(b(b(B(x0)))))))))))) → B1(b(a(b(b(b(a(b(b(b(B(x0)))))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 1 SCC with 3 less nodes.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(b(b(b(b(b(b(x0))))))) → B1(a(b(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(b(x0))))) → B1(a(b(a(b(b(b(x0)))))))
B1(b(b(b(a(b(b(a(b(b(b(B(x0)))))))))))) → B1(a(b(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(b(b(x0)))))))) → B1(b(a(b(a(b(b(b(x0))))))))
B1(a(b(b(a(b(a(b(x0)))))))) → B1(b(b(a(b(b(x0))))))
B1(a(b(b(a(b(b(b(b(x0))))))))) → B1(b(a(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(a(b(b(a(b(x0))))))))) → B1(a(b(b(b(b(a(b(b(x0)))))))))
B1(a(b(b(a(b(a(b(b(b(B(x0))))))))))) → B1(b(b(a(b(b(a(b(b(B(x0))))))))))
B1(a(b(b(a(b(b(b(b(b(b(B(x0)))))))))))) → B1(b(a(b(b(a(b(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(a(b(b(a(b(b(b(B(x0)))))))))))))) → B1(b(a(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(b(b(b(b(b(x0)))))) → B1(a(b(b(a(b(b(b(x0))))))))
B1(a(b(b(a(b(a(b(b(a(b(x0))))))))))) → B1(b(a(b(b(b(a(b(b(x0)))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule B1(a(b(b(a(b(a(b(b(b(B(x0))))))))))) → B1(b(b(a(b(b(a(b(b(B(x0)))))))))) at position [0] we obtained the following new rules:
B1(a(b(b(a(b(a(b(b(b(B(y0))))))))))) → B1(b(b(b(a(b(b(b(B(y0)))))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(b(b(b(b(b(b(x0))))))) → B1(a(b(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(a(b(b(a(b(b(b(B(x0)))))))))))) → B1(a(b(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(b(b(x0)))))))) → B1(b(a(b(a(b(b(b(x0))))))))
B1(a(b(b(a(b(a(b(x0)))))))) → B1(b(b(a(b(b(x0))))))
B1(a(b(b(a(b(b(b(b(b(b(B(x0)))))))))))) → B1(b(a(b(b(a(b(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(b(b(b(x0))))))))) → B1(b(a(b(b(a(b(b(b(x0)))))))))
B1(a(b(b(a(b(a(b(b(a(b(b(b(B(x0)))))))))))))) → B1(b(a(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(b(b(b(b(b(x0)))))) → B1(a(b(b(a(b(b(b(x0))))))))
B1(a(b(b(a(b(a(b(b(a(b(x0))))))))))) → B1(b(a(b(b(b(a(b(b(x0)))))))))
B1(b(b(b(b(x0))))) → B1(a(b(a(b(b(b(x0)))))))
B1(a(b(b(a(b(a(b(b(b(B(y0))))))))))) → B1(b(b(b(a(b(b(b(B(y0)))))))))
B1(b(b(b(a(b(b(a(b(x0))))))))) → B1(a(b(b(b(b(a(b(b(x0)))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 1 SCC with 1 less node.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
B1(b(b(b(b(b(b(x0))))))) → B1(a(b(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(b(x0))))) → B1(a(b(a(b(b(b(x0)))))))
B1(b(b(b(a(b(b(a(b(b(b(B(x0)))))))))))) → B1(a(b(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(b(b(x0)))))))) → B1(b(a(b(a(b(b(b(x0))))))))
B1(a(b(b(a(b(a(b(x0)))))))) → B1(b(b(a(b(b(x0))))))
B1(a(b(b(a(b(b(b(b(x0))))))))) → B1(b(a(b(b(a(b(b(b(x0)))))))))
B1(b(b(b(a(b(b(a(b(x0))))))))) → B1(a(b(b(b(b(a(b(b(x0)))))))))
B1(a(b(b(a(b(b(b(b(b(b(B(x0)))))))))))) → B1(b(a(b(b(a(b(b(b(a(b(b(B(x0)))))))))))))
B1(a(b(b(a(b(a(b(b(a(b(b(b(B(x0)))))))))))))) → B1(b(a(b(b(b(a(b(b(a(b(b(B(x0)))))))))))))
B1(b(b(b(b(b(x0)))))) → B1(a(b(b(a(b(b(b(x0))))))))
B1(a(b(b(a(b(a(b(b(a(b(x0))))))))))) → B1(b(a(b(b(b(a(b(b(x0)))))))))
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
We have reversed the following QTRS:
The set of rules R is
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
The set Q is empty.
We have obtained the following QTRS:
b(b(b(b(x)))) → b(b(b(a(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
B(b(b(b(b(b(b(x))))))) → B(b(b(a(b(b(b(a(b(x)))))))))
B(b(b(b(a(b(b(a(b(x))))))))) → B(b(b(a(b(b(a(b(b(x)))))))))
B(b(b(b(b(a(b(x))))))) → B(b(b(b(a(b(b(x)))))))
The set Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(b(b(a(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
B(b(b(b(b(b(b(x))))))) → B(b(b(a(b(b(b(a(b(x)))))))))
B(b(b(b(a(b(b(a(b(x))))))))) → B(b(b(a(b(b(a(b(b(x)))))))))
B(b(b(b(b(a(b(x))))))) → B(b(b(b(a(b(b(x)))))))
Q is empty.
We have reversed the following QTRS:
The set of rules R is
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
b(b(b(b(b(b(B(x))))))) → b(a(b(b(b(a(b(b(B(x)))))))))
b(a(b(b(a(b(b(b(B(x))))))))) → b(b(a(b(b(a(b(b(B(x)))))))))
b(a(b(b(b(b(B(x))))))) → b(b(a(b(b(b(B(x)))))))
The set Q is empty.
We have obtained the following QTRS:
b(b(b(b(x)))) → b(b(b(a(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
B(b(b(b(b(b(b(x))))))) → B(b(b(a(b(b(b(a(b(x)))))))))
B(b(b(b(a(b(b(a(b(x))))))))) → B(b(b(a(b(b(a(b(b(x)))))))))
B(b(b(b(b(a(b(x))))))) → B(b(b(b(a(b(b(x)))))))
The set Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(b(b(a(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
B(b(b(b(b(b(b(x))))))) → B(b(b(a(b(b(b(a(b(x)))))))))
B(b(b(b(a(b(b(a(b(x))))))))) → B(b(b(a(b(b(a(b(b(x)))))))))
B(b(b(b(b(a(b(x))))))) → B(b(b(b(a(b(b(x)))))))
Q is empty.
We have reversed the following QTRS:
The set of rules R is
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
The set Q is empty.
We have obtained the following QTRS:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
The set Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
Q is empty.
We have reversed the following QTRS:
The set of rules R is
b(b(b(b(x1)))) → b(b(b(a(b(x1)))))
b(a(b(b(a(b(x1)))))) → b(b(a(b(b(x1)))))
The set Q is empty.
We have obtained the following QTRS:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
The set Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(b(x)))) → b(a(b(b(b(x)))))
b(a(b(b(a(b(x)))))) → b(b(a(b(b(x)))))
Q is empty.